The Effect of Hospital Image and Service Quality on Patient Loyalty through Satisfaction as an Intervening Variable in the Outpatient Unit Sawit Indah Perbaungan General Hospital - Hakim, Farhana Abdul; Situmorang, Syafrizal Helmi; Sembiring, Beby Karina Fawzeea (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the factors influencing patient loyalty at Sawit Indah General Hospital in Perbaungan, focusing on the role of hospital image, service quality, and patient satisfaction. Using a quantitative approach with an associative method, this research connects the variables of hospital image (X1), service quality (X2), patient satisfaction (Z), and patient loyalty (Y) to examine the relationships among these variables. Data were collected through questionnaires, interviews, and documentation, and then analyzed using descriptive statistical analysis and path modeling with Structural Equation Modeling (SEM) and Partial Least Squares (PLS) methods. The results show that hospital image and service quality significantly affect patient satisfaction, which in turn influences patient loyalty. This research is expected to provide insights for hospital management to improve patient satisfaction and loyalty, as well as contribute to the sustainability of the hospital's operations.